2013
DOI: 10.1111/jpn.12029
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of ruminal fermentation and methane production by supplementation of rain tree pod meal containing tannins and saponins in growing dairy steers

Abstract: Four rumen-fistulated dairy steers were used in a 2 × 2 factorial arrangement in a 4 × 4 Latin square design. The main factors were two roughage-to-concentrate ratios (R:C, 60:40 and 40:60) and two supplementation levels of rain tree pod meal (RPM) [0 or unsupplemented and 60 g/kg of total dry matter (DM) intake]. Chopped 30 g/kg of urea-treated rice straw was used as a roughage source. All animals received dietary according to respective R:C ratios at 25 g/kg body weight. The RPM contained condensed tannins a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
3
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 28 publications
1
26
3
1
Order By: Relevance
“…Anantosook et al. () observed that with rations of high quality with a forage to concentrate ratio of 60:40, microbial CP synthesis and the efficiency of microbial nitrogen synthesis were greater compared to rations with a 40:60 forage to concentrate ratio.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Anantosook et al. () observed that with rations of high quality with a forage to concentrate ratio of 60:40, microbial CP synthesis and the efficiency of microbial nitrogen synthesis were greater compared to rations with a 40:60 forage to concentrate ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Anantosook et al. (), with better quality rations with a ratio of 60:40 forage to concentrate and with the incorporation of 60 g/kg of Samanea saman , found that the excretion of urinary allantoin was increased by 15.29%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations